UN peacekeeping in action : the Namibian experience - Hearn, Roger (Commack, N.Y. : Nova Science Publishers, 1999)
"The settlement of Namibia's long running conflict remains one of the major successes of the United Nations. Over the course of one year, UN peacekeepers assisted the people of Namibia to gain their independence after years of oppressive South African rule. This book provides an in depth study of the conditions contributing to the UN's success in Namibia and what these reveal about peacekeeping and peace enforcing in other contexts."--Jacket.
A Short-Lived Success -- Developing a New Understanding of UN Peacekeeping -- A History of Occupation -- Resolution 435 and UNTAG -- Violence and Intimidation in Namibia -- The Military Component of UNTAG -- The Role of the Special Representative's Office in Preventing Violence and Intimidation -- The UN Police in Namibia -- Creating the Conditions for Free and Fair Elections -- The Electoral Process and Independence -- Impacts and Perceptions -- The Effectiveness of UNTAG -- App. 2. Resolution 435.
Includes bibliographical references (pages 255-266) and index.
Keywords: United Nations -- Armed Forces -- Namibia -- History -- 20th century; Geschichte 1946-1990.; 1900-1999; Armed Forces; Politics and government; Transition to independence